Chronic disease medication management at home: a quantitative survey among 180 patients - Sabine Bayen; Yolaine Haegeman; Nassir Messaadi; Marc Bayen; Maurice Ponchant; Anthony Haro; François Quersin; Matthieu Calafiore (BJGP Open)
Background: In France, 40% of people aged >16 years (20 million) report having at least one chronic disease requiring long-term treatment. Compliance with treatment at home is estimated to be 50% on average. Aim: To study the practical management of oral treatments at home by people living with one or more chronic diseases. Design & setting: A quantitative, descriptive, observational, cross-sectional study. Thirty GPs in France were invited by email to enrol 10 consecutive patients with chronic diseases. Method: Standardised questionnaires were used to assess the sociodemographic profile of doctors and patients, and the management of oral medication at home. Results: Twenty GPs collected 180 questionnaires of which 70% responders said they did not find taking their medication a problem; 43% used a pillbox; 79% said they knew 'all' their medications; and 61% reported forgetting to take their medication (versus 30% who reported never forgetting to take their medication). Conclusion: More than half of patients are non-adherent to taking oral medication at home for their long-term conditions. Personalised reminders could reduce unintentional medication non-adherence.